Translation Initiation from Conserved Non-AUG Codons Provides Additional Layers of Regulation and Coding Capacity - Ivaylo P. Ivanov (American Society for Microbiology, 2017)
ABSTRACT Neurospora crassa cpc-1 and Saccharomyces cerevisiae GCN4 are homologs specifying transcription activators that drive the transcriptional response to amino acid limitation. The cpc-1 mRNA contains two upstream open reading frames (uORFs) in its >700-nucleotide (nt) 5′ leader, and its expression is controlled at the level of translation in response to amino acid starvation. We used N. crassa cell extracts and obtained data indicating that cpc-1 uORF1 and uORF2 are functionally analogous to GCN4 uORF1 and uORF4, respectively, in controlling translation. We also found that the 5′ region upstream of the main coding sequence of the cpc-1 mRNA extends for more than 700 nucleotides without any in-frame stop codon. For 100 cpc-1 homologs from Pezizomycotina and from selected Basidiomycota, 5′ conserved extensions of the CPC1 reading frame are also observed. Multiple non-AUG near-cognate codons (NCCs) in the CPC1 reading frame upstream of uORF2, some deeply conserved, could potentially initiate translation. At least four NCCs initiated translation in vitro. In vivo data were consistent with initiation at NCCs to produce N-terminally extended N. crassa CPC1 isoforms. The pivotal role played by CPC1, combined with its translational regulation by uORFs and NCC utilization, underscores the emerging significance of noncanonical initiation events in controlling gene expression. IMPORTANCE There is a deepening and widening appreciation of the diverse roles of translation in controlling gene expression. A central fungal transcription factor, the best-studied example of which is Saccharomyces cerevisiae GCN4, is crucial for the response to amino acid limitation. Two upstream open reading frames (uORFs) in the GCN4 mRNA are critical for controlling GCN4 synthesis. We observed that two uORFs in the corresponding Neurospora crassa cpc-1 mRNA appear functionally analogous to the GCN4 uORFs. We also discovered that, surprisingly, unlike GCN4, the CPC1 coding sequence extends far upstream from the presumed AUG start codon with no other in-frame AUG codons. Similar extensions were seen in homologs from many filamentous fungi. We observed that multiple non-AUG near-cognate codons (NCCs) in this extended reading frame, some conserved, initiated translation to produce longer forms of CPC1, underscoring the significance of noncanonical initiation in controlling gene expression.